The social life of gender - Ray, Raka; Carlson, Jennifer; Andrews, Abigail (SAGE Publications, Inc., 2018)
KEY FEATURES: The text is driven by an interest in unequal relations of power and how gender informs and is reinforced in institutions and other large-scale historical processes. Global perspectives are woven throughout book for today's increasingly globalized students. The book focuses on understanding not just gender but the social world through a gendered lens. The practical application of theoretical themes shows specific arenas of life not necessarily considered "gendered" on the surface